Reconstruction of rocks petrophysical properties as input data for reservoir modeling. (16th November 2016) - Cantucci, B.; Montegrossi, G.; Lucci, F.; Quattrocchi, F.
Abstract: The worldwide increasing energy demand triggered studies focused on defining the underground energy potential even in areas previously discharged or neglected. Nowadays, geological gas storage (CO2 and/or CH4 ) and geothermal energy are considered strategic for low‐carbon energy development. A widespread and safe application of these technologies needs an accurate characterization of the underground, in terms of geology, hydrogeology, geochemistry, and geomechanics. However, during prefeasibility study‐stage, the limited number of available direct measurements of reservoirs, and the high costs of reopening closed deep wells must be taken into account. The aim of this work is to overcome these limits, proposing a new methodology to reconstruct vertical profiles, from surface to reservoir base, of: (i) thermal capacity, (ii) thermal conductivity, (iii) porosity, and (iv) permeability, through integration of well‐log information, petrographic observations on inland outcropping samples, and flow and heat transport modeling. As case study to test our procedure we selected a deep structure, located in the medium Tyrrhenian Sea (Italy). Obtained results are consistent with measured data, confirming the validity of the proposed model. Notwithstanding intrinsic limitations due to manual calibration of the model with measured data, this methodology represents an useful tool for reservoir and geochemical modelers that need to define petrophysical input data for underground modeling before the well reopening. Key Points: Reconstruction of heat capacity, thermal conductivity, permeability, and porosity, integrating well‐log information and numerical modeling Results show that the proposed method is valid and can be applied in other areas Petrophysical data may be used as main input data for reservoir modeling during prefeasibility studies